Brand Endorsement: Comparison of the Influence of Bloggers and Celebrities in Attitude Regarding Brand - Bravo, Bruna Santos (2018)
Objective:This study compares if celebrities and bloggers influence is the same on the attitude towards the brand and measures which of them have higher credibility as endorser, based on the consumer's opinion. Method: Experiment Relevance/Originality:The literature review did not present causal models comparing the effects of celebrities and bloggers. Also, there were conflicting views: on the one hand, the view that blogger and celebrity would be at different levels regarding their power and extent of influence in the attitude towards the brand they endorse; on the other hand, the prospect of a change in this situation would be underway and that both could be equated, since, in addition to the credibility of the source, the cultural meaning is a relevant factor in the success of the endorsement tactic. Main results:Unlike the previous literature, but in line with the latest evidence on the market, the results showed that there is no significant difference in attitude toward the brand if the brand endorsement is performed by a celebrity or blogger. Additionally, they present equivalent levels of credibility. Contribuitions: This study contributes to the understanding of the role of traditional celebrities and a digital influencer type, the blogger, and their effects on brand endorsement tactics, adding to the prevailing theoretical model the perspective that the cultural meaning cannot be ignored in the attribution of credibility to endorsers.